THE NATURAL OCCURRENCE OF PENICILLIUM SPP. METABOLITES IN MAIZE KERNELS ORIGINATING FROM SERBIA - Kos, Jovana (Food and Feed Research, 2022)
Maize can be contaminated with a wide range of fungal secondary metabolites that decrease the quality and safety of maize and maize-derived products. The increase of natural fungal metabolites occurrence in maize, influenced by climate changes, is recognized as a significant issue in recent years. Therefore, the main aim of this study was to investigate the influence of weather conditions on the natural occurrence of Penicillium spp. metabolites in maize kernel samples. The survey was conducted for two maize vegetation seasons 2016 and 2017. In total 458 maize samples were analyzed by liquid chromatography-tandem mass spectrometry method. The samples originated from the Autonomous Province of Vojvodina, and regions of Bačka, Srem, and Banat. Among 45 Penicillium metabolites investigated 16 and 18 were detected in samples from 2016 and 2017, respectively. The most commonly occurring Penicillium metabolite in both years was oxaline, which was detected in more than 90% of analyzed samples. Questiomycin A, 7-hydroxypestalotin, pestalotin, and mycophenolic acid were also very frequently detec-ted Penicillium metabolites. This is one of the unique studies in the Republic of Serbia, as well as in this part of Europe, investigating the occurrence of a great number of Penicillium metabolites in maize samples.